Characteristic Analysis of Coal Oil Mixture as Alternative Diesel Fuel from Low Rank Coal at PT.Nusa Alam Lestari Site Sinamar Dharmasraya Sumatera Barat - Deni Syahputra; Rijal Abdullah; Yunasril Yunasril (Journals Mining Engineering : Bina Tambang, 2018)
Coal oil mixture (COM) is one of the methods of making liquid coal fuel in addition to liquefaction and coal water fuel. Coal oil mixture (COM) is a mixed fuel with a balanced composition between coal, petroleum, and additives (Maeda, 1991: 66).In this study, the coal used is low rank coal mixed with additives and diesel. The ratio of coal: diesel: the additives used are 25%: 75%: 0% (COM A1), 25%: 74%: 1%, (COM A2) and 25%: 73%: 2% (COM A3).The results showed that the viscosity characteristics tested on COM A1, A2, A3 were closer to MDO than HFO as standard ISO 8217 2010 MDO (Marine Diesel Oil) viscosity with maximum limit of 11 cSt at 400c temperature. The calorific value of COM A1, A2, A3 is lower than MDO due to the utilization of low calorie coal in the mixture.